The Association Between Smoking History and Intensive Phase Treatment Success of Pulmonary Tuberculosis Patients in Dr. Zainoel Abidin Hospital Banda Aceh - Risa Fitria; Feni Fitriani Taufik; Dewi Behtri Yanifitri (Jurnal Respirologi Indonesia, 2018)
Background: Many diseases are associated with smoking such as malignant disease, cardiovascular, diabetes mellitus (DM), chronic obstructive pulmonary disease (COPD), arthritis, impotence, infertility, Alzheimer’s Disease, tuberculosis and others. Smoking is proven to disrupt the ciliary mucosal clearance and it is associated with an increased risk of pulmonary tuberculosis. Sputum conversion is an important indicator to assess the success of TB treatment. This study aims to determine the relation between smoking history and the success intensive phase treatment of pulmonary tuberculosis at Dr Zainoel Abidin Hospital. Method: Prospective cohort study in patients with pulmonary tuberculosis acid-fast bacilli (AFB) positive (+) smokers and non smokers who visited the Integrated Tuberculosis Care (PTT), at outpatient and inpatient pulmonary infection RSU Dr. Zainoel Abidin hospital Banda Aceh from 28 November 2015 until 1 February 2016. Results: A total of 38 subjects were divided into 2 groups (19 subjects with 19 subjects smokers and non-smokers). All subjects smokers are male while nonsmoker subjects consisted of male and female. The results of the first month study (p=0.009), there are 14 non smoker subjects with AFB conversion (73,7%) and 5 subjetcs without AFB conversion. Among smoking subjects there are 6 subjets (31.6%) with AFB conversion and 13 subjects (68.4% ) without AFB conversion. In the second month (p=0,202), more than half subjects who are non-smokers had AFB conversion, 17 subjects (89.5%) and 2 subjects (10.5%) had no AFB conversion. In smokers group there are 14 subjects (73.7% ) had AFB conversion and 5 subject (26.3%) had no conversion. Conclusion: There was a significant relation between smoking habit and the occurrence of first-month AFB sputum. (J Respir Indo. 2018; 38: 232-8)